Pemanfaatan Daun Sendok (Plantago Major L.) Untuk Pengobatan Asam Urat Masyarakat Jalan Tirtasari 1 Kelurahan Margasari Kecamatan Buahbatu - Fadhila Rahma Irawan; Tri Cahyanto (Institut Nalanda, 2024)
One of the potential plants that can be utilized as traditional medicine is spoon leaves. broadleaf plantain (Plantago major L.) are included in the category of wild plants or wild medicinal plants. This study aims to examine the use of broadleaf plantain or ki urat leaves as a treatment for gout arthritis in the Tirtasari community, Margasari village, Buahbatu sub-district. The method used in this study is an observation technique, namely interviews with a sampling of 15 selected through pursive sampling techniques and documentation and literature study approaches. The broadleaf plantain in the Tirtasari community this plant is called ki urat leaf can be found in a variety of habitats, including in fields, roadsides, gardens, and other open areas. The results of this research found that the Tirtasari community has two ways of using this broadleaf plantain for alternative treatment of gout arthritis, namely 9 samples using direct rubbing and 6 samples using the results of mashed spoon leaves that are rubbed on the body that feels sore. These two ways of use have the same treatment effect but differ in texture and absorbency. This broadleaf plantain has many compounds that are beneficial to the health of the body, namely anti-inflammatory, diuretic, and antioxidant compounds.